Inflammatory Cells Can Alter the Levels of H3K9ac and γH2AX in Dysplastic Cells and Favor Tumor Phenotype - Barbeiro, Camila de Oliveira [UNESP]; Fernandes, Darcy [UNESP]; Palaçon, Mariana Paravani [UNESP]; Castilho, Rogerio Moraes; de Almeida, Luciana Yamamoto [UNESP]; Bufalino, Andreia [UNESP] (MDPI, 2023)
Oral potentially malignant disorders (OPMD) are clinical presentations that carry an increased risk of cancer development. Currently, epithelial dysplasia grade is based on architectural and cytological epithelial changes and is used to predict the malignant transformation of these lesions. However, predicting which OPMD will progress to a malignant tumor is very challenging. Inflammatory infiltrates can favor cancer development, and recent studies suggest that this association with OPMD lesions may be related to the etiology and/or aggressive clinical behavior of these lesions. Epigenetic changes such as histone modifications may mediate chronic inflammation and also favor tumor cells in immune resistance and evasion. This study aimed to evaluate the relationship between histone acetylation (H3K9ac) and DNA damage in the context of dysplastic lesions with prominent chronic inflammation. Immunofluorescence of “low-risk” and “high-risk” OPMD lesions (n = 24) and inflammatory fibrous hyperplasia (n = 10) as the control group was performed to assess histone acetylation levels and DNA damage through the phosphorylation of H2AX (γH2AX). Cell co-culture assays with PBMCs and oral keratinocyte cell lines (NOK-SI, DOK, and SCC-25) were performed to assess proliferation, adhesion, migration, and epithelial–mesenchymal transition (EMT). Oral dysplastic lesions showed a hypoacetylation of H3K9 and low levels of γH2AX compared to control. The contact of dysplastic oral keratinocytes with PBMCs favored EMT and the loss of cell–cell adhesion. On the other hand, p27 levels increased and cyclin E decreased in DOK, indicating cell cycle arrest. We conclude that the presence of chronic inflammation associated to dysplastic lesions is capable of promoting epigenetic alterations, which in turn can favor the process of malignant transformation.
Keywords: co-culture; epithelial dysplasia; malignant transformation; peripheral blood mononuclear cell